Development of Trustworthy Cyber-Physical Systems : Artificial Intelligence's Viewpoint - Tolvanen, Joel (2020)
This Master’s Thesis assesses how companies developing Artificial Intelligence are pursuing its trustworthiness. Artificial Intelligence is widely used when implementing Cyber-Physical Systems, that are coupling computational capabilities with the ability to control and sense the physical space. By gaining the access of physical environment, unexpected operation of Cyber-Physical Systems with AI capabilities can cause critical damage to environment and even human beings. Due to this, AI systems should be lawful, ethical and reliable. This research was conducted using the Ethics guidelines defined by European Commission, that provided the conceptual framework for assessment of trustworthiness of prevailing practices. Empirical qualitative research was conducted within Finnish companies developing Artificial Intelligence. Findings of the study suggest that trustworthiness is mainly pursued by realizing accountability, transparency and technical robustness of the system, whilst realization of societal and environmental wellbeing and diversity, nondiscrimination and fairness were not brought into attention. For realizing the neglected requirements, managerial advice is provided.